Fuzzy topology - Palaniappan, N. (Alpha Science International Ltd., 2005)
This book imparts latest developments in various properties of fuzzy topology viz., fuzzy set theory, fuzzy point and its neighbourhood structure, Fuzzy nets and Fuzzy convergence, Fuzzy metric, Different fuzzy compactness, Fuzzy connectedness, Fuzzy separation axioms and properties, Product spaces, Convex fuzzy sets and Fuzzy uniform spaces